Impoliteness Strategies Between Main Characters in the Modified Song Lyric of a Motion Picture - Olivia, Najwa Syaqila; Heriyati, Nungki (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This study aims to analyze impoliteness strategies in the film “How to Lose a Guy in 10 Days” . Using a qualitative approach, this research examines Andie’s and Ben’s modified lyrics of Carly Simon’s "You're So Vain" using Culpeper’s (1996) impoliteness strategies then Austin’s (1962) speech acts theory before categorising impoliteness strategies used in the data. The discussions reveal that positive and bald on record impoliteness emerge as the two equally dominant strategies, followed by negative impoliteness. These findings suggest that the characters primarily utilize a mix of filtered and unfiltered attacks to heighten interpersonal conflict in a public setting. This study concludes that altered song lyrics serve as intentional face-threatening tools in cinematic climaxes. This research implies that song lyrics in films can function as powerful pragmatic tools to negotiate power and express protest through modified lyrics.